KINERJA BADAN PENANGGULANGAN BENCANA DAERAH DALAM MITIGASI BENCANA KEBAKARAN HUTAN DI KABUPATEN TANJUNG JABUNG BARAT PROVINSI JAMBI - Fiqra, Muhammad; NOVELLA, YESSY (Institut Pemerintahan Dalam Negeri, 2023)
The author focuses on the problem where disasters are unpredictable but can still be prevented and anticipated, especially forest fires which have become an annual agenda during the dry season, therefore the role of the government and the community is needed. The purpose of this study was to determine the performance and inhibiting factors of BPBD performance and to determine BPBD's efforts in Tanjung Jabung Barat Regency in dealing with factors that hindered the implementation of forest fire disaster mitigation in Tanjung Jabung Barat Regency, Jambi Province. This study uses a descriptive qualitative method with an inductive approach and analysis of the performance theory of Agus Dwiyanto. Data collection techniques using in-depth interviews (17 informants), documentation and observation. Facilities and infrastructure owned by the Regional Disaster Management Agency of Tanjung Jabung Barat Regency are still very lacking. This can be seen from the obstruction of BPBD in accessing the location of the forest fire disaster. In addition, the number of facilities and infrastructure used in disaster mitigation is still small. That the performance of the BPBD of Tanjung Jabung Barat Regency is generally good and continues to make progress towards improving services to the community. The author provides criticism and suggestions for the Regional Disaster Management Agency of Tanjung Jabung Barat Regency to continue to improve towards a better direction to answer the demands of the community. Keywords: Disaster;BPBD;Forest Fire;Performance